A chromosome-level genome assembly of Serangium japonicum Chapin, 1940 (Coleoptera: Coccinellidae) - Maolin Ye; Yonghui Xie; Jianfeng Jin; Chuyang Huang; Kaide Ning; Zhengling Liu; Hongming Li; Xingmin Wang (Scientific Data)
Abstract Serangium japonicum (Coleoptera; Coccinellidae) plays a crucial role as a predatory coccinellid in ecosystems, exhibiting adept predation on diverse whitefly species and effectively regulating their population dynamics. Nonetheless, the absence of high-quality genomic data has hindered our comprehension of the molecular mechanisms underlying this predatory beetle. This study performed genome sequencing of S. japonicum using the PacBio HiFi long reads and Hi-C data. The genome spans 433.74 Mb, which includes 104 contigs and 17 scaffolds, with a contig N50 size of 11.44 Mb and a scaffold N50 size of 42.67 Mb. A substantial portion of the genome, totaling 433.04 Mb (99.84%), was anchored to 10 chromosomes. BUSCO analysis demonstrates a high genomic completeness of 97.8% (n = 1,376), comprising 97.3% single-copy genes and 0.5% duplicated genes. The genome includes 54.66% (237.06 Mb) repetitive elements and 12,299 predicted protein-coding genes. The chromosome-level genome of S. japonicum offers important genomic insights that enhance our understanding of the evolution and ecology of the Coccinellidae family.